Dietary intake of 337 polyphenols in French adults - Pérez-Jiménez, Jara; Fezeu, Léopold; Touvier, Mathilde; Arnault, Nathalie; Manach, Claudine; Hercberg, Serge; Galan, Pilar; Scalbert, Augustin (The American journal of clinical nutrition, 2011)
Background: Epidemiologic studies have suggested an association between polyphenol intake and health. These studies have been limited to ≤40 flavonoid and lignan aglycones.Objective: We estimated intakes of all known individual polyphenols in the French cohort SUpplémentation en VItamines et Minéraux AntioXydants (SU.VI.MAX) by using the recently developed database Phenol-Explorer, which contains content values for 502 polyphenols in 452 foods.Design: A total of 4942 men and women, who were aged 45–60 y and who had completed at least six 24-h dietary records, participated in this study. Foods documented in 24-h dietary records and the Phenol-Explorer database were matched, and intakes of all individual polyphenols were calculated.Results: A total of 337 polyphenols were consumed by SU.VI.MAX subjects, including 258 polyphenols consumed by at least one-half of the population and 98 polyphenols consumed in an amount >1 mg/d. Mean total polyphenol intake was estimated at 1193 ± 510 mg/d (or 820 ± 335 mg/d when expressed as aglycone equivalents), with hydroxycinnamic acid esters and proanthocyanidins being the most largely consumed polyphenols. These values may have been underestimated because of insufficient data or lack of accurate data on the content in foods for proanthocyanidins and thearubigins. Nonalcoholic beverages and fruit were the most important contributors to polyphenol intakes.Conclusions: The current study provides intake data for all individual polyphenols known to be present in the diet of a cohort. This information will be essential to characterize the health effects of individual phenolic compounds that differ widely in their bioavailability and physiologic properties. The SU.VI.MAX study was registered at clinicaltrials.gov as NCT00272428.